86 Evaluation of the effect of prenatal transportation stress on endocrine and immune tissues of neonatal Brahman calves. (28th November 2020) - Earnhardt, Audrey L; Wellman, Catherine L; Hairgrove, Thomas; Cardoso, Rodolfo C; Long, Charles R; Riley, David G; Randel, Ron; Welsh, Thomas H
Abstract: The objective of this experiment was to evaluate whether prenatal transportation stress (PNS) affects the weight of endocrine and immune tissues of calves. Mature Brahman cows inseminated to a single Brahman sire in 2018 were assigned to be either Control (n = 35; not transported) or PNS (n = 37; 2 h of transportation at 60, 80, 100, 120, and 140 ± 5 d of gestation). Of the calves born in 2019, 16 Control (8 bulls and 8 heifers) and 16 PNS (8 bulls and 8 heifers) calves were studied. Pen score, body weight, and blood samples were obtained from calves at 25 ± 2 d of age. At that time, calves were euthanized by barbiturate overdose in order to collect tissues (brain, pituitary and adrenal glands, spleen and thymus). Tissues were trimmed and weighed. Serum cortisol was determined by RIA. Data were analyzed using ANOVA, GLM, and CORR procedures of SAS with body weight at sample collection as a covariate. Whole pituitary weight tended (P = 0.08) to be greater in females compared to males, whereas anterior pituitary weight tended (P = 0.06) to be greater in PNS. Whole brain weight was greater (P < 0.01) in males. The interaction of treatment and sex on whole brain weight of PNS tended (P = 0.09) to fall between that of the Control females and Control males. Whole pituitary weight was positively correlated with total adrenal weight (r = 0.32; P = 0.08). Total thymus weight positively correlated with whole brain and total adrenal weight (r = 0.43 and 0.41, respectively; P < 0.05). Serum cortisol was negatively correlated with spleen weight and total immune tissue weight (r = -0.37 and -0.38, respectively; P < 0.05). Results suggest next steps should include a closer look at function of immune tissues by studying PNS effect on thymus response to immunization.